Propozycja segmentacji w oparciu o koncepcję łańcuchów celów i środków na przykładzie wybranych regionów europejskich - Sobczak, Elżbieta (The Proposal of Segmentation Based on Means-End Chains Concept using the Example of Selected European Regions, 2006)
The objective of the hereby study is the proposal of regional segmentation taking advantage of multidimensional statistical analysis and the means-end-chain concept, possible for application by enterprises seeking for competitive foreign markets. An attempt was also taken up to illustrate empirically the discussed research procedure based on the example of selected European NUTS-2 type regions.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1124, s. 86-95